Methods Of Processing Oxford Nanopore Sequencing Data For Metagenomics - Barilíková, Lujza (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2018)
The presented paper describes a new method of processing data produced by revolutionary sequencing technology introduced by Oxford Nanopore Technologies – MinION, which holds a great promise in the field of metagenomics. Low cost, produced long reads and portability, due to its small dimensions, represents only one of the many advantages of this technology. Despite of the benefits, there is a lack of available computational tools for handling the produced data and that is the reason, why a new method of processing such data should be created. In this study such method is created based on dimensionality reduction for data visualization.
Keywords: metagenomics; Oxford Nanopore; nanopore sequencing; dimensionality reduction